"Keeping It Real": The Relational Effects of Trauma Among African American Women and Their Substance Abuse Treatment Counselors. (September 2020) - Blakey, Joan M.; Grocher, Kimberly B.
African American women experience disproportionately high rates of trauma. Interpersonal forms of trauma often make it much more difficult for trauma survivors to initiate and maintain positive, healthy relationships with others. This study examined the kinds of relationships women with extensive histories of trauma and substance had with their substance abuse treatment counselors and the characteristics that they believe contributed to connected and disconnected client–counselor relationships. Using the case study method, 26 in-depth interviews were conducted with African American women. Data analysis revealed three primary kinds of relationships women had with their substance abuse treatment counselors: reparative, damaging, and transactional. Eighteen (69%) of the 26 women had reparative relationships with their counselors. Reparative relationships had two primary characteristics: empowering and mattering. Two (8%) of the 26 women had damaging relationships with their substance abuse treatment counselors. Damaging relationships had two primary characteristics: unimportant and untrustworthy. Six of the women (23%) had transactional relationships with their substance abuse treatment counselors. Transactional relationships were task-focused and superficial. Healing from interpersonal experiences of trauma is possible only within the context of trusting relationships. Substance abuse treatment counselors have an opportunity to help African American women with histories of trauma heal and recover. Creating positive, therapeutic relationships between clients and professionals is essential.